Análise do transcriptoma de folhas de cana-de-açúcar submetidas à prolongada limitação hídrica usando RNA-Seq - Belesini, Aline Andrucioli [UNESP] (2015)
In Brazil, the sugarcane culture has expanded to areas with prolonged drought seasons, which is constraining sugarcane production. In this study, the gene expression profiles of two sugarcane cultivars (Saccharum spp.), one tolerant and other sensitive to water stress, were assessed by the RNA-Seq technology. The de novo assembly of leaves transcriptome was held aiming to identify and to analyze differentially expressed genes between the cultivars involved with molecular response during water stress periods. In order to accomplish this, the two cultivars were planted in a greenhouse and 60 days after planting them, they were submitted to three potential controlled water soil (control, moderate drought and severe water deficit) and evaluated at 30, 60 and 90 days after treatments application. Using the RNA-Seq method were generated over a billion sequences, which allowed to obtain a total of 177,509 and 185,153 transcripts sequences for the tolerant and sensitive cultivars, respectively. The set of expressed transcripts were assembled using the Trinity program. These transcripts were aligned with Sorghum bicolor, Miscanthus giganteus, Arabidopsis thaliana sequences and sugarcane sequences available in public databases. This analysis allowed the identification of the set of sugarcane genes shared with other species, as well as led to the identification of novel transcripts not cataloged yet. The transcripts were annotated and categorized by the terms of the Gene Ontology (GO) into three categories: cellular component, molecular function and biological process for the two cultivars. The terms enzyme regulator and transcription regulator that lie within the molecular function category are highlighted within the terms associated with the differentially expressed genes between the contrasting cultivars, suggesting the importance of gene regulation for the studied cultivars. This study found different molecular patterns of the involved ...